ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL BUFFER (Studi Kasus pada Bank Umum Konvensional yang Terdaftar di BEI Tahun 2011-2014) - Fauzia, Nanda Arum; Idris, Idris (Diponegoro Journal of Management, 2016)
Capital buffer is difference between ratio of the bank’s capital to the minimum capital adequacy ratio that appropriate with central bank’s regulation. Capital buffer can be used by banks as buffer in adverse economic shocks. This study aims to examine the influence of  Return on Equity (ROE), Non Performing Loan (NPL), Loans over Total Asset (LOTA), GDP Growth (GDPG), and lag of capital buffer (BUFFt-1) to capital buffer level of Conventional Banks were listed on Bursa Efek Indonesia.In this study the population is 41 commercial banks were listed on Bursa Efek Indonesia. The selection of the sample is by using purposive sampling method with some specific criteria and sample that used are 30 conventional commercial banks were listed on Bursa Efek Indonesia period 2011-2014. The analysis method is by using multiple linear regression analysis.The result show that Return on Equity (ROE) has positive correlation and insignificant with capital buffer. Non Performing Loan (NPL) and GDP growth (GDPG) has negative correlation with capital buffer and insignificant. Loans over Total asset (LOTA) has negative and significant correlation with capital buffer and lag of capital buffer (BUFFt-1) has positive and significant correlation with capital buffer. The result of regression estimation show whole variable have ability of model prediction is 51,7%, while remaining is 48,3%  influenced by other faktors outside the model.